Wintering Waterbirds in the Wetlands of the Azov-Black Sea Region of Ukraine at the Beginning of the 21st Century — Species Composition, Abundance, Distribution and Tendencies - Andryuschenko , Yu. O.; Kostiushyn, V. A. (Publishing House "Akademperiodyka" of the National Academy of Sciences of Ukraine, 2024)
Data collection on wintering waterbirds in the wetlands of the Azov-Black Sea region of Ukraine began in the late 1980s, mainly thanks to the International Waterbird Census (IWC), which has become more extensive and regular since about 2005. This article is devoted to generalization of data on species composition, abundance of birds and their spatial distribution in that region based on the results of the winter census 2005–2022. The long-term dynamics of the waterbirds number and the peculiarities of the species distribution are mostly analyzed for abundant bird species. General information about common and rare species is also given.